Förtolkning inför skogsbruksplanläggning med laserdata (NNH), eller traditionell flygbildstolkning? - Boden, Pehr (2014)
The purpose of this study was to investigate produced laser data from the new national height model's airborne laser scanning in Sweden, what quality it has and whether it can be used for forest management planning. From airborne laser scanning one can obtain information on forest variables such as tree species, height, diameter and basal area. Norra skogsägarna is the principal employer of this project and they wanted know to the quality of the laser data which needs to cope with their standards. If the laser data the quality required it can replace some of the operations performed by field planners.